Application of Customer Development Model and Financial Feasibility Analysis For Teaching Entrepreneurial Feasibility Study at STP Bogor: Toward To Vocational Pedagogy of Entrepreneurial Learning - Hastjarjo (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: There is a need for future methods and fields of study to enrich and complement vocational education in the field of business and entrepreneurship in Indonesia today so that students can improve their competence.Purpose: This article provides an overview of the development, structure, and results of the entrepreneurial feasibility study course at STP Bogor which uses entrepreneurial learning methods. Design/methodology/approach: This research is classroom action research. Business model canvas (BMC) and customer development model (CDM) in entrepreneurship are integrated with financial feasibility analysis (FFA) in feasibility studies. Analytical tools using teaching methods are case-based examples, team-based learning combined with initial case studies, one business idea for each class, learning by doing, and planning posters and pitch deck presentations. The research method used is qualitative participatory action research, students are the main respondents who work on and produce practical assignments to analyze their understandingFindings/Result: Case-based examples, team-based learning combined with initial case studies, one business idea for each class, learning by doing, and pitch deck presentations can be used as pedagogy to teach entrepreneurial feasibility studies. This methods are suitable for studying entrepreneurship.  Conclusion: Following students throughout the course has shown that the entrepreneurship course directly strengthens students' skills by enabling them to start their own businesses.Originality/value (State of the art): The study found that combining experiential teaching approaches, such as case-based examples, team-based learning, one business idea for each class, learning by doing, planning posters, and presentation sessions.Keywords:    feasibility study, entrepreneurship, business model canvas, customer development, financial feasibility analysis